Aplikasi Layanan Kesehatan Gigi Berbasis Website Pada Klinik Dokter Gigi Tooth Art Kota Malang - Afifah Fauziah; Linda Suvi Rahmawati; Sri Esti Trisno Sami (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2026)
The Tooth Art Dentist Clinic in Malang City recently addressed critical challenges regarding dental service accessibility. Previously, the clinic relied on conventional registration methods and physical medical records. These manual processes were time-consuming, causing long patient queues and increasing the risk of data errors, which hindered medical personnel from providing prompt care. To overcome these hurdles, the clinic implemented a sophisticated website-based application designed for patients, administrators, and doctors. The platform focuses on several core functionalities: Online Registration and Reservations, Electronic Medical Record Management, Online Transactions, and a Public Educational Platform.The implementation has resulted in a substantial increase in operational efficiency. Patients can now manage their own bookings, effectively eliminating long waiting times. Furthermore, the transition to electronic records ensures that patient data is accurate and instantly accessible. Beyond clinical operations, the application serves as a vital educational tool, providing the community with valuable information on dental hygiene. Consequently, this digital transformation has successfully improved service accessibility while fostering better health awareness, providing a modern solution for dental healthcare in Malang City.